Reconciling humans with nature : using Marx's dialectical materialism to critically explore philosophy and politics in contemporary environmentalism and to develop a perspective on environmental justice - Jordi, Richard (Department of Environmental and Geographical Science, 2015)
Bibliography : leaves 152-161.